Isozoanthus antumbrosus, a new species of zoanthid (Cnidaria: Anthozoa: Zoanthidea) symbiotic with Hydrozoa from the Caribbean, with a key to hydroid and sponge-symbiotic zoanthid species - Swain, Timothy D. (Zootaxa, 2009)
Isozoanthus antumbrosus, a new species of zooxanthellate zoanthid, is described. Colonies associate with the arborescent hydroid Dentitheca dendritica in the Caribbean Sea at 1–60 m. The coenenchyme, column, and oral disk are seal brown. The tentacles are golden brown and number 30–38. The coloration of the oral disk and tentacles recalls an annular solar eclipse. Polyps are 4.1–8.9 mm long and 2.2–4.3 mm in diameter. Genetic, morphological, and ecological characters differentiate this species from other hydroid-symbiotic zoanthids. Assignment to the genus Isozoanthus is based on morphology, with the acknowledgment that the currently accepted genera may not reflect evolutionary relationships.